"Being a good patient" during times of illness as defined by adolescent patients with cancer. Issue 14 (3rd May 2016) - Weaver, Meaghann S.; Baker, Justin N.; Gattuso, Jami S.; Gibson, Deborah V.; Hinds, Pamela S.
Abstract : BACKGROUND: Adolescents with cancer cite the opinions of others and expected impact on others as formative for their care preferences and decisions. The current study first explores how the concepts of being a good child and being a good patient may exist for adolescents with cancer and determines how adolescents describe and apply these concepts. The study then investigates parental actions and clinician behaviors perceived by adolescents with cancer as supportive in helping them to achieve their defined good child and good patient roles. METHODS: In a prospective study conducted at 2 cancer treatment centers over the course of 10 months, 40 adolescents with cancer responded to 10 open‐ended questions. Semantic content analysis was used. An adolescent focus group validated the findings. RESULTS: Of the 40 participants in the current study, 39 confirmed 1 or both concepts; the good patient responses yielded 112 codes and 5 themes: cooperation, adherence, communication, self‐care, and care for others. The good child responses revealed 88 codes and 7 themes: cooperation and respect, positivity, lightening others' burdens, taking treatment seriously, recognizing mutual impact, communication, and acknowledging mortality. Of 589 interview phrases, 184 (31%) depicted themes of care for others and 58 (10%) spoke of tolerating treatment in the hope of a better future for one's self or others. The benefits and challenges of living up to these definitions were discussed. CONCLUSIONS: Clinicians may consider asking adolescents about their "good child" and "good patient" descriptions to learn more about the perceived roles carried by adolescents with cancer and how these roles may impact their decision making, medication adherence, and social interactions. Cancer 2016;122:2224–33 . © 2016 American Cancer Society . Abstract : Adolescents with cancer consider relational roles in their medical interactions, citing the opinions of others and impact on others as formative for their care preferences and decisions. This face‐to‐face interview study describes "good patient" and "good child" terms through interviews with 40 adolescent oncology patients. The adolescents' description of the concepts plus the behaviors of parents and professionals is reported. The study reports on parental actions and clinician behaviors perceived by adolescents with cancer as supportive in helping them to achieve their good child and good patient definitions.